A global empirical analysis on the diffusion & innovation of carbon pricing policies. (15th August 2022) - Raghoo, Pravesh; Shah, Kalim U.
Abstract: There are 45 countries which have adopted a kind of carbon pricing policy – either a carbon tax or entered a cap–and–trade or both – while other countries do not have such policies implemented. As carbon pricing policies are considered as an effective lever to mitigate climate change, there is a need to understand what factors are motivating countries to adopt a carbon pricing policies and what factors might limit such endeavor. There is thus a need to examine how carbon pricing policies get adopted cross–nationally to examine pathways for climate change mitigation and incentivize other countries to follow. In this study, a model combining both internal and external diffusion factors is built (how one countries adoption of a carbon pricing policy affects another) to identify factors of adoption of carbon pricing policies. An Event History Analysis approach was used by compiling data for 127 countries running from 1990 to 2019. The findings show that the carbon pricing policies diffuse mainly through learning from neighboring countries and to a slight degree, by imitation. With a split sample analysis to account for policy heterogeneity, it was seen that both the carbon tax and the cap–and–trade system diffuse through the learning mechanism, however for the cap–and–trade, the policy can also diffuse through coercion and normative pressure if countries are part of EU. It was also found from the regressions that adoption of the carbon pricing policy by a country is motivated by a democratic political regime and from the level of coal production in the country. Among other groups, this finding is important for the international climate advocacy groups to decide which countries are more likely to adopt such policies where they can push forward this agenda.